Emerging technological and cultural shifts advancing drylands research and management. Issue 1 (1st February 2015) - Browning, Dawn M; Rango, Albert; Karl, Jason W; Laney, Christine M; Vivoni, Enrique R; Tweedie, Craig E
Abstract : Sustainable management of arid landscapes is complicated by extreme conditions that constrain biological responses to perturbation, great spatial complexity, and uncertain degrees of ecosystem resilience to climate change. Traditional approaches to the collection, management, and analysis of data from dryland monitoring efforts should consider these complications. Over the past century, research on drylands has gradually transitioned from short‐term, plot‐scale studies to long‐term, regional‐ and biome‐scale efforts. Two thresholds are imminent: a technological tipping point that will facilitate performing novel science using new techniques to collect, manage, and analyze data, and a cultural tipping point, where various research products are shared more freely and through different communication pathways. A new framework could be developed by promoting interdisciplinary collaboration and implementing standardized practices regarding data collection, curation, and sharing.